Multi-succedent sequent calculus for intuitionistic epistemic logic - Alonderis, Romas (Lietuvos matematikos rinkinys, 2024)
A multi-succedent sequent calculus for intuitionistic epistemic logic (IEL) is introduced in the paper. It is  proved that the structural rules of weakening and contraction and the rule of cut are admissible in the  calculus. It is also proved that any sequent with at most one formula in succedent is derivable in the  calculus, iff it is derivable in the standard non-multi-succedent sequent calculus of IEL.
Keywords: intuitionistic epistemic logic; sequent calculus